Influence of Different Therapy on Hematological Markers and Fertility Response in Anestrus Sahiwal Cows - Husain, Safayat; Kumar, Rajesh; Singh, Bhoopendra; Srivastava, Sushant; Kumar, Rabindra; Kumar, Pramod; Srivastava, Ashish (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study was designed to evaluate influence of different therapy on hematological markers, resumption of ovarian cyclicity and conception rate in 24 anestrus Sahiwal cows, which were randomly and equally allocated to four groups as G1, G2, G3 and G4. Lugols iodine (2%, cervical painting with per rectal massage of genitalia thrice on alternate day) XXX herbal bolus (1 bid for 2 days, repeated on day 11 & 12 later in non-respondents) and modified ovsynch protocol (progesterone 100 mg s/c once a day for 6 days followed by GPG) was administered in G1, G2 and G3, respectively, while G4 kept as untreated control. All these animals were dewormed with bolus fenbendazole 3 g plus ivermectin 100 mg, once and supplemented with mineral mixture 30 g/day for 21 days before above therapies. Blood samples were collected thrice, i.e., on day 0, day of induced estrus/AI and day 21 post-AI (day 0, 21 and 63 in non-respondents) for hematological analysis. In general, hemogram and leucogram did not vary significantly within and among different groups, except neutrophil and lymphocyte. Cent per cent estrus induction response was observed in treatment group G1, G2 and G3, however, none of the cows resumed cyclicity in untreated control group G4. The treatment to estrus induction interval was 9.17±2.34, 8.33±2.36 and 16±0.00 days; treatment to fertile estrus interval was 33.6±8.40, 42.0±8.57 and 29.4±5.14 days and overall conception rate was 83.33, 66.66 and 83.33 % in group G1, G2 and G3, respectively, while nil in untreated anestrus cows.